Sleep efficiency and duration assessed with metabolic holter: associate with body composition and dietary components: Sleep efficiency and duration - Acar Tek, Nilüfer; Navruz Varlı, Semra; Karaçil Ermumcu, Merve Şeyda; Ertaş Öztürk, Yasemin (Progress in Nutrition, 2020)
Objective: This study was planned to determine the associations between sleep duration, efficiency,quality with dietary components in adults. Methods: This cross-sectional study was conducted with youngadults aged between 19-30 years. Sleep duration and efficiency were assessed with Metabolic Holter. Sleepquality was assessed with Pittsburgh Sleep Quality Scale. Three consecutive days’ dietary record was taken atthe same time with metabolic holter. Body composition was analyzed with Bioelectric Impedance Analysis.Results: Body fat mass, body fat percent, waist circumference, and waist/hip ratio was found higher in femaleswith poor sleep efficiency, and decreased sleep efficiency correlated with increased waist/hip ratio (r=-0.324;p=0.054). Being female gender and decreased fat mass were shown as major predictors for increased sleepefficiency according to regression analyses. Also, in females with poor sleep quality had higher percentage ofbody fat mass and body mass index than females with good sleep quality (p